ANALISIS KENYAMANAN PENGEMBANGAN PRODUK MEJA SETRIKA MENGGUNAKAN RAPID UPPER LIMB ASSESSMENT (RULA) - Adi Nugroho, Septa; Ina Siti Hasanah (Universitas Majalengka, 2024)
The development of the ironing table product that is currently made only uses the same design, there is no difference in terms of shape or form and there are not many additional functions. This study aims to identify the size of the ironing table with anthropometry, create a design for developing an ironing table and product development after being folded into a chair, and measure the comfort of product development with a product reference using Rapid Upper Limb Assessment (RULA). In this study, anthropometry was used to determine the size of the product to be made, and Rapid Upper Limb Assessment (RULA) was used to identify and compare the comfort between reference products and products being developed. The results of the introduction of the ironing table product size using anthropometry are the height of the ironing table of 105 cm, the height and width of the ironing table of 50 cm, the length of the ironing table of 120 cm, the height of the chair seat of 40 cm, the width of the chair seat of 60 cm, the length of the chair seat of 50 cm, and the height of the chair backrest as high as 125 cm. Based on the results of the comfort analysis using RULA, it can be seen that the development product has a smaller value compared to the reference product, so the conclusion is that overall the development product is more comfortable to use than the reference product.